Baclofen dose-dependently disrupts learning in a place avoidance task requiring cognitive coordination - Stuchlik, Ales; Vales, Karel (Physiology & behavior, 2009)
The active place avoidance task is a cognitive task requiring spatial learning and cognitive coordination. In this task, animals are trained to move over a continuously rotating arena, on which an imperceptible to-be-avoided sector is defined, remaining stable with respect to the experimental room. The present study was aimed at evaluating the effect of GABA-B receptor agonist baclofen on locomotion and spatial behavior in active place avoidance task. Baclofen (at doses 2, 3, 3.5, 4 and 6 mg/kg) was applied 30 min prior to testing in the task. Doses 2 mg/kg and 3 mg/kg were found not to interfere with either locomotion or spatial avoidance; a dose 3.5 mg/kg disrupted selectively spatial behavior, and doses 4 mg/kg and 6 mg/kg proved to decrease both avoidance efficiency and locomotor activity. It is concluded that GABA-B receptor agonist baclofen dose-dependently disrupts spatial learning and locomotion in the place avoidance task.
Keywords: Analysis of Variance; Animals; Baclofen; vztah mezi dávkou a účinkem léčiva; reakční čas; Rats, Long-Evans; Avoidance Learning; chování zvířat; GABA Agonists; baklofen; Locomotion; poruchy učení; Learning Disabilities; Spatial Behavior; lokomoce; Dose-Response Relationship, Drug; analýza rozptylu; potkani Long-Evans; Male; učení vyhýbat se; krysa rodu Rattus; Behavior, Animal; Reaction Time; GABA agonisté; zvířata; mužské pohlaví; Rats; prostorové chování